Effects of Iron-Steel Factory and Dense Traffic on Leaf Chemical Compounds of Six Tree Species in Turkey - Turfan, Nezahat; Savaci, Gamze; Sarıyıldız, Temel (Kastamonu Univ, Orman Fak, 2018)
Aim of study: Tree planting can play an important role in improving the quality of the urban environment. On the other hand, air pollutants can affect growth and health of trees. We studied the impacts of air pollution caused by the iron-steel factory and dense traffic on leaf chemical composition and also tree tolerance to the air pollution using six tree species (Maple, Ash tree, Cypress, Black pine, Sycamore and Aspen). Material and Methods: The fresh leaf and needle sampling was carried out in April and July, and analyzed for photosynthetic pigments, peroxidation level, hydrogen peroxide, enzymatic antioxidants and non-enzymatic antioxidants. Main results: Although there were statistically significant variations in the studied chemical compositions of the fresh leaf and needle samples between the six tree species, the pollution types and time, each chemical factor acted different ways with the pollution types and time according to tree species. In general, the pigment values, MDA, H2O2 and APX, concentrations in July were lower than those in April, whereas CAT, SOD, proline and protein concentrations in July were higher than those in April. Maple tree was more resistant to the traffic pollution, while Ash tree was more tolerant to both the pollution types. Among all trees, Aspen was found more susceptible to the traffic pollution Research highlights: The results could be used in the future research directions to improve our understanding of the role of individual tree species in air pollution reduction and also set up a healthy, well managed urban forest which can provide many ecological benefits to urban environment.
Keywords: Air pollution; Chemical composition; Dense traffic; Iron-steel factory; Forest tree